THE CHILDHOOD TRAUMA OF KATIE IN “MOCKINGBIRD DON’T SING”FILM - Garin Allif Arya Aditya; Milisi Sembiring (Fakultas Sastra UMN AL Washliyah, 2022)
Film as a work of art has several elements of art in order to fulfill spiritual needs which not only serves to entertain the audience but also to provide some kind of education or knowledge about certain things. The primary data in this study is to analyze a film entitled Mockingbird Don't Sing by Harry Bromley Davenport and written by Daryl Haney. The main purpose of this study is to describe violence against children, the main character's traumatic behavior, and the causes of the main character's traumatic behavior due to violence against children or child abuse. The method used qualitative method in the research to explain the data, collect data by watching movies repeatedly and then find to Identify data. The classify the data in the table based on the problem of violence regarding children, factors causing traumatic behavior and mental disorders. The analyzed the data using a psychological approach.